A water‐soluble acrylamide hydrophobically associating polymer: Synthesis, characterization, and properties as EOR chemical. Issue 4 (25th December 2012) - Lai, Nanjun; Dong, Wan; Ye, Zhongbin; Dong, Jun; Qin, Xiaoping; Chen, Weili; Chen, Ke
Abstract A water‐soluble acrylamide hydrophobically associating terpolymer for polymer flooding was successfully synthesized via free radical polymerization using acrylamide (AM), acrylic acid (AA), and N, N‐divinylnonadeca‐1, 10‐dien‐2‐amine (DNDA) as raw materials. The terpolymer was characterized by IR spectroscopy and fluorescence spectra. Compared with partially hydrolyzed polyacryamide (HPAM), the terpolymer showed a stronger link and better dimensional network structure under the environmental scanning electron microscope (ESEM). The results of rheology indicated that the terpolymer (AM‐NaAA‐DNDA) showed an excellent shear‐resistance in high shear rate (1000 s−1) and remarkable temperature‐tolerance (above 110°C). The salt‐resisting experiment revealed that this terpolymer had a better anti‐salt ability. According to the core flooding test, it could be obtained that oil recovery was enhanced more than 15% under conditions of 2000 mg/L terpolymer in the mineralization of 8000 mg/L at 60°C. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013